Calving time and foetus growth among wild reindeer in Norway - Reimers, Eigil (Rangifer, 2002)
Mean calving dates among 7 wild reindeer (Rangifer t. tarandus) herds in southern Norway varied between the 6th and the 27th of May. Ln transformed foetus weights relate linearly to ln age in days. Regression analyzes based upon 225 days pregnancy predicts birth wet weights between 4600 and 7500 g in the different areas and years. At 130 days, foetus weights varied between 547 and 746 g (mean=681, standard deviation s=63) in all areas and years, indicating that foetus growth up to this size is independent of mothers body weight or condition. During the remaining 95 days of pregnancy, very poor body condition, reflected in dressed weights, resulted in slower foetus growth and smaller regression estimated birth weights. The foetus weight variation recorded at similar dates within areas and sampling years indicates a dispersed breeding time mostly within two ovulations. A small sample of foetuses from pregnant yearlings and calves indicate that these cohorts conceive later than 2 yr + females. Assuming similar foetus growth pattern among all female age cohorts within areas, yearlings conceive around 1 week later and calves (in Ottadalen) more than 3 weeks later than 2 + yr olds.